Independent Calibration of Radar Reflectivities Using Radiosondes: Application To ESRAD - Kirkwood, Sheila; Mihalikova, Maria; Mikhaylova, Daria; Wolf, Ingemar; Chilson, Phillip (Polar Atmospheric Research, Swedish Institute of Space Physics, Box 812, 98128 Kiruna, Sweden, 2011)
A large number of empirical and theoretical studies haveshown that radar reflectivity from the atmosphere at 50MHz is proportional to the mean vertical gradient of therefractive index. Up to 30 km height the refractive indexis determined by temperature, pressure and humidityprofiles, which can readily be measured by radiosondes.In practice, humidity becomes unimportant abovethe mid-troposhere. The coefficient of proportionality betweenradar reflectivity and mean refractive index gradientshould, in principle, depend on the fine-scale structureof refractive index fluctuations. However, recent empiricalevidence shows that the coefficient varies very littlebetween widely different meteorological conditions andbetween radars in very different locations (Esrange, tropicalIndia, Antarctica). This means we can use meanprofiles of refractive index, measured by radiosondes, asan independent method to provide continuous calibrationof radar reflectivity and to cross-calibrate between differentradars without the need to interrupt operations for thekind of engineering tests which are usually used for calibration.We show how this can be applied for long-termcalibration of the 52 MHz atmospheric radar at Esrange,ESRAD.The observed invariability of the coefficient of proportionalityalso poses an intriguing question as to how it canbe explained. High-resolution sondes, constant-heightsondes, and UAV’s are suggested as suitable platformsfor further study of the radar scattering mechanisms. Upprättat; 2011; 20160622 (andbra)